Analisis Strategi Pemasaran Produk Industri Kerajinan Kain Tenun Songket Di Desa Pringgasela Kabupaten Lombok Timur - Muhammad, Farhana; Susilawati, Susilawati; Uliya, Rafiza (Universitas Hamzanwadi, 2023)
This research aims to determine the strategies used to market the products of the songket woven cloth craft industry in Pringgasela Village by collecting data using observation, interviews and documentation using a descriptive qualitative approach. using the SWOT analysis method. Based on the research results, it is known that the marketing strategy carried out by the Songket Woven Fabric Craft Industry in Pringgasela Village, East Lombok Regency is to maintain the quality of raw materials, as well as woven motifs and patterns. Songket Woven Cloth Craft Product Industry in Pringgasela Village, East Lombok Regency has different prices in terms of the complexity of the pattern.